PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN DAN LUAS WILAYAH TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kabupaten/Kota di Jawa Tengah Tahun 2014-2016) - Sapti Dwi Mukti, 15.05.52.0320; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the effect of Local Revenue, Balancing Funds, and the Regional Area on Capital Expenditure with Economic Growth as moderating variable on regency / city goverments in Central Java Province for period 2014-2016. The population in this study is regency / city goverments in Central Java Province which consists of 29 regency and 6 city. Techniques in sampling using census method. This study uses secondary data in the form of budget realization report, economic growth and regional area. Analytical technique used is Moderated Regression Analysis. The results showed that Local Revenue does not significantly affect on Capital Expenditure. Balancing Funds has a positive and significant effect on Capital Expenditure. Regional Area has a negative and significant effect on Capital Expenditure. Economic Growth does not moderate the effect of Local Revenue on Capital Expenditure. Economic Growth moderate the effect of Balancing Funds and Regional Area on Capital Expenditure.